Vitrificação e cultivo in vivo de tecido ovariano de cutias (Dasyprocta leporina, Lichtenstein, 1823) - Praxedes, Erica Camila Gurgel (2017)
The objective of the present thesis was to use the manipulation of oocytes enclosed in preantral follicles (MOIFOPA) as a tool for the female gametes rescue and conservation, from wild species agouti (Dasyprocta leporina). The dissertation was divided into two experimental phases. At first, it was performed solid surface vitrification (SSV) using different concentrations of cryoprotectant agents (CPAs) in which the effects of the 3 and 6 M concentrations of dimethylsufoxide (DMSO) and ethylene glycol (EG) were verified, as well as the association of both CPAs in the high concentration (6 M) under morphology, viability and apoptosis cell on the in situ PFs. A total of 865 PFs was analyzed before and after vitrification, it was observed an average of 80.7 ± 5.21% of morphologically normal follicles in the control group and after SSV, indifferent the CPA used, it was possible to preserve until 76.7% ± 5.4 OF PFs. At viability analysis, DMSO 3 M, DMSO 6 M, EG 3, EG 6 M (70.0%, 81.11%, 76.6% and 71.11%, respectively) presented similar values to the control group (79.0%). No apoptotic cells (TUNEL positive) were found before and after vitrification. At second, vitrification was performed using the association of CPAs, followed by xenografting of ovarian tissue in C57Bl/6 SCID Black mice. Through vaginal washing monitoring, was observed that 80% mice of the xeno-fresh group and 42% of the xeno-vitrified group returned to ovarian activity, confirmed by hormonal measures. Microscopically, primordial, primary and transitional follicles were observed in the grafts, and all had normal morphology for the species studied. However, major primordial and primary follicles were observed in transplants. The NORs revealed that after transplantation a significant reduction (1.66 ± 0.25) occurred when compared to the control groups (group fresh control: 7.19 ± 1.23 and xeno-fresh group: 9.10 ± 0.64). Apoptotic cells (TUNEL positive) were found only after transplantation of samples vitrified and the healthy follicles (TUNEL negative) observed in other groups (TUNEL negative). Thus, as the general conclusion, the use of MOIFOPA in agouti allowed the knowledge of aspects related to its reproductive morphology and physiology, enabling the germplasm conservation, with the possibility of germplasm bank formation, as the elucidation of mechanisms related to the PF survive and in vivo development